Toward an American Conservatism : Constitutional Conservatism during the Progressive Era - Postell, Joseph; O'Neill, Johnathan; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
This volume seeks both to give constitutional conservatives their first full treatment, and to demonstrate the ongoing relevance of early conservatives to contemporary American conservatism.
Keywords: Science; Science; Science, general